2013
DOI: 10.1371/journal.pone.0053662
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Glycyrrhetinic Acid on Carbon Tetrachloride-Induced Chronic Liver Fibrosis in Mice via Upregulation of Nrf2

Abstract: This study was designed to investigate the potentially protective effects of glycyrrhetinic acid (GA) and the role of transcription factor nuclear factor-erythroid 2(NF-E2)-related factor 2 (Nrf2) signaling in the regulation of Carbon Tetrachloride (CCl4)-induced chronic liver fibrosis in mice. The potentially protective effects of GA on CCl4-induced chronic liver fibrosis in mice were depicted histologically and biochemically. Firstly, histopathological changes including regenerative nodules, inflammatory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 61 publications
3
91
1
1
Order By: Relevance
“…Several studies indicated that up-regulation of Nrf2 expression can elevate SOD and CAT mRNA levels in mouse liver [64] and GR mRNA levels in rat lung [65]. Interestingly, the present study showed that arginine deficiency and excess caused an upregulation of Nrf2 mRNA expression level in juvenile Jian carp intestine, which exhibited an opposite pattern with SOD1, CAT and GR mRNA levels.…”
Section: Arginine Regulated the Intestinal Antioxidant Capacity Via Ncontrasting
confidence: 40%
“…Several studies indicated that up-regulation of Nrf2 expression can elevate SOD and CAT mRNA levels in mouse liver [64] and GR mRNA levels in rat lung [65]. Interestingly, the present study showed that arginine deficiency and excess caused an upregulation of Nrf2 mRNA expression level in juvenile Jian carp intestine, which exhibited an opposite pattern with SOD1, CAT and GR mRNA levels.…”
Section: Arginine Regulated the Intestinal Antioxidant Capacity Via Ncontrasting
confidence: 40%
“…The correlation analysis showed that CuZnSOD and GR mRNA levels were positively related to Nrf2 mRNA level (r CuZnSOD ¼ þ0.831, P CuZnSOD < 0.05; r GR ¼ þ0.953, P GR < 0.01) in the gills of young grass carp, indicating that riboflavin deficiency decreased CuZnSOD and GR mRNA levels may be partly by decreasing Nrf2 mRNA level in the gills of fish. It was reported that Nrf2 was sequestered by its suppressor Keap1 in the cytoplasm which prevented Nrf2 nuclear translocation in mice [29]. Devling et al [85] reported that the down-regulation of Keap1 gene expression could promote the nuclear translocation of Nrf2, and subsequent increased antioxidant enzymes gene expression in HaCaT cells.…”
Section: 42mentioning
confidence: 99%
“…To our knowledge, antioxidant enzyme activities partly rely on antioxidant enzyme mRNA expression [28]. Meanwhile, antioxidant enzymes genes expression has proven to be regulated by Nrf2 signaling pathway in mice [29]. Therefore, we next investigated the effects of riboflavin on antioxidant enzymes mRNA expression and Nrf2 signaling pathway in the gills of fish.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CCl 4 is well known to degrade DNA in liver tissue of rats by generating free radicals and increase DNA fragmentation (Alkreathy et al, 2014). Regarding the gene expression level, the current findings indicated that, CCl 4 induced down-regulation of the examined antioxidant enzymes (SOD and GPx) gene expression and liver fibrosis in mice (Chen et al, 2013). The genotoxic effects of AgNPs were represented by the increase in DNA fragmentation and the disturbance of gene expression which may be attributed to oxidative stress created by AgNPs exposure.…”
Section: Disscustionmentioning
confidence: 60%